Malian children infected with Plasmodium ovale and Plasmodium falciparum display very similar gene expression profiles. - Kieran Tebben; Salif Yirampo; Drissa Coulibaly; Abdoulaye K Koné; Matthew B Laurens; Emily M Stucke; Ahmadou Dembélé; Youssouf Tolo; Karim Traoré; Amadou Niangaly; Andrea A Berry; Bourema Kouriba; et al. (Public Library of Science (PLoS), 2023)
Plasmodium parasites caused 241 million cases of malaria and over 600,000 deaths in 2020. Both P. falciparum and P. ovale are endemic to Mali and cause clinical malaria, with P. falciparum infections typically being more severe. Here, we sequenced RNA from nine pediatric blood samples collected during infections with either P. falciparum or P. ovale, and characterized the host and parasite gene expression profiles. We found that human gene expression varies more between individuals than according to the parasite species causing the infection, while parasite gene expression profiles cluster by species. Additionally, we characterized DNA polymorphisms of the parasites directly from the RNA-seq reads and found comparable levels of genetic diversity in both species, despite dramatic differences in prevalence. Our results provide unique insights into host-pathogen interactions during malaria infections and their variations according to the infecting Plasmodium species, which will be critical to develop better elimination strategies against all human Plasmodium parasites.